Taken by the Shawnee - Bingham, Sallie (Turtle Point Press, 2024)
"A most unusual portrait of early America based on a rare family document, in which a young mother's years in captivity with the Shawnee prove to be the best years of her life. It's 1779 and a young white woman named Margaret Erskine is venturing west from Virginia, on horseback, with her baby daughter and the rest of her family. She has no experience of Indians, and has absorbed most of the prejudices of her time, but she is open-minded, hardy, and mentally strong, a trait common to most of her female descendants--Sallie Bingham's ancestors. Bingham had heard Margaret's story since she was a child but didn't see the fifteen pages Margaret had dictated to her nephew a generation after her captivity until they turned up in her mother's blue box after her death. Devoid of most details, this restrained account inspired Bingham to research and imagine and fill the gaps in her story and to consider the tough questions it raises. How did Margaret, our narrator, bear witnessing the murder of her infant? How did she survive her near death at the hands of the Shawnee after the murder of the chief? Whose father was her baby John's, born nine months after her taking? And why did her former friends in Union West Virginia turn against her when, ransomed after four years, she reluctantly returned? This is the seldom told story of the making of this country in the years of the Revolution, what it cost in lives and suffering, and how one woman among many not only survived extreme hardship, but flourished"--